Diplomatie en geweld De internationale context van de Indonesische onafhankelijkheidsoorlog, 1945-1949 - Kemperman, Jeroen (Amsterdam University Press, 2022)
Lecturing the Dutch in public probably makes them more stubborn rather than less stubborn. And they are already stubborn enough,' wrote a British diplomat in July 1947. How did the United States, the United Kingdom and France view the Indonesian War of Independence in the period of 1945-1949? Did they show understanding for the Dutch political and military policies or rather for the Indonesian position, and in what ways did they try to influence the parties? Where did the Dutch get their military equipment to wage war in Indonesia? In 'Diplomatie en geweld', the authors show how other countries and the recently founded United Nations were involved in the Dutch-Indonesian conflict and how they helped determine its course and outcome. In doing so they focus not only on the political and diplomatic aspects of the struggle, but also on foreign views on the use of violence by the Dutch armed forces